The Asymmetric Effects of Inflation and Interest Rates on MSMEs in Indonesia - Sunaryono Sunaryono; Zulimi Zulimi (Jurnal Ekonomi STIEP, 2026)
This study examined the long-term and short-term impacts of interest rate policy (BI Rate) and inflation on the development of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Using annual time-series data from 1997 to 2023, the Vector Error Correction Model (VECM) was applied to capture both equilibrium relationships and dynamic adjustments among the variables. Stationarity tests confirmed that the variables were integrated of mixed orders, and the Johansen cointegration test revealed the existence of long-run relationships. The results showed that inflation had a more substantial and statistically significant effect on MSME performance in the short run, particularly through lagged effects. In contrast, the BI Rate had a limited and statistically insignificant influence, suggesting that inflation posed a more immediate constraint on MSME growth. The significant error correction term confirmed that MSMEs adjusted gradually to deviations from long-term equilibrium. These findings highlighted the need for inflation-targeted policies and improved financial access mechanisms to support MSME resilience. The study concluded that macroeconomic stability, especially price control, played a more critical role than monetary tightening in shaping MSME outcomes. It also suggested that expanding alternative financing, such as peer-to-peer lending and digital credit solutions, could buffer MSMEs from macroeconomic volatility. This research contributed to the existing literature by providing empirical evidence from a developing country context and suggested future exploration of digital financial tools as adaptive strategies for MSMEs.